Hemovigilance: knowledge, attitude and practice among postgraduates and interns of a tertiary care hospital - Ram, Sandosh; T., Indushree; D., Meghana; Yohini, Geetha (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Adverse reactions due to transfusion of blood and blood products should be reported for the betterment of patients health and to minimize such effects in the future. A Program was initiated to report and reduce incidence of adverse reactions to blood products which is hemovigilance program of India. Aim was to evaluate the knowledge, attitude and practice of haemovigilance among postgraduates and interns. Methods: This was a cross-sectional questionnaire-based study conducted among 159 participants of a tertiary care hospital for a period of 1 month. Results: Results obtained were analysed using descriptive and qualitative statistics. About 83.6% of the participants were aware about the concept of Haemovigilance. Only 23 out of the 159 had reported transfusion reactions in the past but the attitude towards this concept was satisfactory. Conclusions: Overall the participants had a less satisfactory overview of this concept and hence educational interventions can aid in serving the purpose.